ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) PADA MATERI KURIKULUM PENDIDIKAN EKONOMI DI INDONESIA - Jatmiko, Naufal Nur; Syahrudin, Husni; Basri, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study aims to analyze the need for Augmented Reality (AR)-based learning media in the Curriculum Review and Economic Learning Planning course at Tanjungpura University. This study was motivated by the limited interactive learning media that can help students understand abstract material and increase active participation in the learning process. Qualitative methods were used with a case study approach. Data were collected through observation and interviews with lecturers and students involved in the course. The results of the study showed that both lecturers and students needed innovative and contextual learning media. Lecturers said that Augmented Reality (AR)-based learning media can help explain complex curriculum concepts visually and interactively, so that they are easier for students to understand. Meanwhile, students stated that the use of Augmented Reality (AR) media can increase interest in learning, clarify understanding of the material, and provide a more enjoyable learning experience. This study concludes that there is a significant need for the development of Augmented Reality (AR)-based learning media in this course, in order to support the achievement of student competencies optimally. The recommendations from this study are the development of an Augmented Reality (AR) media prototype that suits learning needs, training on media use for lecturers, and integration of Augmented Reality (AR) into curriculum planning. These findings contribute to innovation in economic learning in higher education and encourage the use of digital technology in education.